Reengineering of human resources processes and implementing human resources information system to improve management decision making - Eyüpoğlu, Şerife Esin (My University, 2002)
Yönetmek; planlama, organize etme, liderlik ve kontrol fonksiyonlarını kullanarak şirketin hedeflerine etkin ve verimli bir şekilde ulaşmasını sağlamak olarak tanımlanmaktadır. Yönetim faaliyetini gerçekleştirirken, yöneticiler organizasyonun stratejisi, yapısı, kontrol sistemleri, insan kaynakları gibi bütün alanları ile ilgili kararlar vermektedirler. Yöneticiler, etkin karar verme ve analitik karar alma sürecinin bütün aşamalarında güncel ve doğru bilgiye gereksinim duymaktadırlar. Çalışanlar ve şirket hakkındaki birçok bilgi İnsan Kaynakları Departmanları tarafından temin edilmektedir. Ücret yönetimi ve bordro hazırlama, çalışan bilgilerini tutma, eğitim ve geliştirme, kariyer ve yedekleme planlaması, performans yönetimi ve işe alma-yerleştirme İnsan Kaynakları Departmanlarının temel fonksiyonlarıdır. İnsan Kaynakları Departmanları bir taraftan bu fonksiyonları yerine getirirken bir taraftan da çalışanlarla ilgili her türlü veriyi toplamak, bu verilerden yönetimin karar vermek için ihtiyaç duyduğu bilgileri elde etmek ve bu bilgileri de istenildiği zaman sunmakla yükümlüdürler. Bu bilgileri sağlamakta kullanılan en önemli araçlar, İnsan Kaynakları Bilgi Sistemleridir. Bu nedenle, pek çok şirkette İnsan Kaynakları Bilgi Sistemleri kurulmaktadır. Ne var ki, süreç ve iş akışlarında iyileştirmeler yapılmadan, tek başına İnsan Kaynakları Bilgi Sistemlerinin kurulması, İnsan Kaynakları Departmanlarının verimliliğini arttırmasını sağlamamaktadır. Bu tezde, İnsan Kaynakları fonksiyonları süreç yaklaşımıyla tanımlanarak analiz edilmiştir. Daha sonra, bu süreçler, sürecin paydaşlarına tutarlı ve kaliteli bir hizmet verebilmeleri için yeniden yapılandırılmıştır. Son olarak da bir İnsan Kaynakları Bilgi Sistemi yerleştirme projesi adımları analiz edilmiştir. Tezde anlatılan süreç analizi metoduyla, İnsan Kaynakları süreçlerindeki verimsiz ve gereksiz noktalarla kopuklukların İnsan Kaynakları Bilgi Sisteminin yerleştirilmesinden önce belirlenerek iyileştirilmesi sağlanmıştır. Böylece, İnsan Kaynakları Bilgi Sistemi uyarlaması, verimsiz süreçleri otomasyonu yerine, yeniden yapılandırılmış verimli süreçlere dayandırılmıştır. Bu da yöneticileri ve çalışanları kararlarında destekleyen etkin bir İnsan Kaynakları Yönetim Bilgi Sistemi oluşmasını sağlamıştır.

REENGINEERING OF HUMAN RESOURCES PROCESSES AND IMPLEMENTING HUMAN RESOURCES INFORMATION SYSTEM TO IMPROVE MANAGEMENT DECISION MAKING Management is defined as the attainment of organizational goals in an effective and efficient manner by planning, organizing, leading and controlling. To commit the organization toward particular courses of action, managers make decisions about all aspects of the organization including, strategy, structure, control systems, responses to the environment and human resources. Managers need current and accurate information at all steps of the effective decision making and analytical decision taking process. Human Resources departments are the suppliers of many types of information about employees and organization. The basic functions of Human Resources Departments are; payroll and salary administration, tracking of employee data, organizational management, training and development, career and succession planning, performance management and recruitment. As well as managing these functions effectively, Human Resources Departments have to collect all Human Resources related data, extract necessary information requested by management for effective decision making from this data and make that information available anytime needed. Human Resources Information Systems are the most important tools for Human Resources Departments in providing that information. Therefore, implementing effective Human Resources Information Systems tools, becomes a major concern for many companies. However, implementing Human Resources Information Systems does not increase efficiency of Human Resources Departments, if the inefficiencies in Human Resources processes and workflow are not eliminated. In this thesis, Human Resources functions are treated as a set of processes, and basic Human Resources processes are defined and analyzed. Then these processes are reengineered to develop a coherent and quality Human Resources service to stakeholders. After that, the steps in a Human Resources Information System implementation project are analyzed. With the process analysis methodology applied in the thesis, it becomes possible to determine and eliminate the inefficiencies, redundant steps and gaps in the Human Resources processes prior to Human Resources Information System implementation. Therefore, instead of automating already inefficient processes, Human Resources Information System implementation was based on efficient, reengineered processes. This yielded to an effective Human Resources Information System, which supports managers and employees in their decisions.
Keywords: Bilgi Sistemleri Yönetimi; İnsan Kaynakları